2016
DOI: 10.1038/srep22322
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected Reaction Pathway for butyrylcholinesterase-catalyzed inactivation of “hunger hormone” ghrelin

Abstract: Extensive computational modeling and simulations have been carried out, in the present study, to uncover the fundamental reaction pathway for butyrylcholinesterase (BChE)-catalyzed hydrolysis of ghrelin, demonstrating that the acylation process of BChE-catalyzed hydrolysis of ghrelin follows an unprecedented single-step reaction pathway and the single-step acylation process is rate-determining. The free energy barrier (18.8 kcal/mol) calculated for the rate-determining step is reasonably close to the experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 70 publications
(81 reference statements)
0
10
0
Order By: Relevance
“…However, due to the extremely high computation workload in QM/MM molecular dynamics simulations of enzymatic reactions, low computation levels (such as semi-empirical methods, e.g., SCC-DFTB and PM6) usually have to be applied to the QM region [30]. We noticed that the major parts of computation in the two works supporting the one-step acylation/deacylation mechanism [22,23] were performed with SCC-DFTB in combination of molecular force field CHARMM27. Actually, in a work published in 2017 [21], the hCES1-catalyzed hydrolysis mechanism of d -threo-methylphenidate was studied using SCC-DFTB and the results were compared with those of DFT (B3LYP/6–31G*).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, due to the extremely high computation workload in QM/MM molecular dynamics simulations of enzymatic reactions, low computation levels (such as semi-empirical methods, e.g., SCC-DFTB and PM6) usually have to be applied to the QM region [30]. We noticed that the major parts of computation in the two works supporting the one-step acylation/deacylation mechanism [22,23] were performed with SCC-DFTB in combination of molecular force field CHARMM27. Actually, in a work published in 2017 [21], the hCES1-catalyzed hydrolysis mechanism of d -threo-methylphenidate was studied using SCC-DFTB and the results were compared with those of DFT (B3LYP/6–31G*).…”
Section: Resultsmentioning
confidence: 99%
“…Later in the same work [21], the SCC-DFTB method was optimized by modifying the Mulliken charge and then the two-step acylation mechanism was reproduced using the modified SCC-DFTB (termed “SCC-DFTBMR”). In the computation study of hCES1-catalyzed hydrolysis of cocaine [23] and butyrylcholinesterase-catalyzed hydrolysis of ghrelin [22], the SCC-DFTB method was used without modifications. So, it might be possible that the free energy of tetrahedral intermediates of cocaine and ghrelin were also overestimated, and hence, they seemed like “tetrahedral transition states”.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Computational efforts by Zhan and coworkers showed this process to follow the two-step acylation and deacylation scheme outlined above [ 74 ]. In contrast, work by the same group to model BChE hydrolysis of ghrelin, the hunger hormone, showed a single-step acylation process [ 75 ]. Interestingly, Suarez et al modeled BChE hydrolysis of butyrylcholine, a synthetic molecule that mimics acetylcholine and for which BChE is named [ 3 ], and found that the presence of glycerol or another butyrylcholine in the active site pocket stabilizes the intermediate product after transition state 2 in the deacylation step, which is a complex of BChE with butyric acid [ 76 ].…”
Section: Catalysismentioning
confidence: 99%
“…Several recent studies have supported butyrylcholinesterase (BChE) as a potential ghrelin esterase within human circulation (Brimijoin et al, 2016;Chen et al, 2015Chen et al, , 2017Schopfer et al, 2015). BChE composes a large proportion of total esterase activity in human serum, and recombinantly expressed BChE can hydrolyze ghrelin to desacyl ghrelin (Schopfer et al, 2015;Yao et al, 2016). BChE knock-out mice challenged with a high fat diet exhibit larger weight gain compared to control mice, with associated implications for BChE expression involvement in body energy regulation and weight control (Chen et al, 2015;Li et al, 2008;Schopfer et al, 2015).…”
Section: Ghrelin Esterasesmentioning
confidence: 99%